Discovery of Arbuscular Mycorrhizae in Mosses of the Pottiaceae Family from the Chaco Serrano (Tucumán, Argentina) - Catania, Myriam del Valle (2025)
Arbuscular mycorrhizal fungi (AMF) are symbiotic fungi that associate with the vast majority of terrestrial plants. Among non-vascular plants, while AMF associa tions are well-documented in liverworts and hornworts, there is a broad consensus that symbiotic associations do not occur in mosses. Here, we report the presence of AMF in the living material of mosses found in Chaco Serrano (Tucumán, Argentina). We found all characteristic structures of AMF when establishing an intimate connection with two moss species of Pottiaceae (Bryophyta). While Gertrudiella uncinicoma exhibited AMF with both Arum- and Paris-type morphologies, Pleurochaete luteola only displayed an Arum-type morphology. Plant tissue samples were subjected to high-throughput sequencing for AMF identification. We determined that Rhizophagus irregularis was a clear dominant species in both moss species, with Glomus sp. also being present as a less abundant element. In addition, we also reported the presence of vesicles, arbuscules, and spores adhered to the hyphae and the presence of septate endophytes. This finding expands our understand ing of the interactions between AMF and non-vascular plants and prompt us to further characterize this interaction by considering the diversity of mycorrhizal associations with concurrent implications for the ecology of mosses and the functionality of the ecosystems.